Enumeration of T cells specific for RD1-encoded antigens suggests a high prevalence of latent Mycobacterium tuberculosis infection in healthy urban Indians. - Lalvani, A; Nagvenkar, P; Udwadia, Z; Pathan, A; Wilkinson, K; Shastri, J; Ewer, K; Hill, A; Mehta, A; Rodrigues, C (2001)
Knowledge of the prevalence of latent Mycobacterium tuberculosis infection is crucial for effective tuberculosis control, but tuberculin skin test surveys have major limitations, including poor specificity because of the broad antigenic cross-reactivity of tuberculin. The M. tuberculosis RD1 genomic segment encodes proteins, such as early secretory antigenic target (ESAT)-6, that are absent from M. bovis bacille Calmette-Guérin (BCG) and most environmental mycobacteria. We recently identified circulating ESAT-6-specific T cells as an accurate marker of M. tuberculosis infection. Here, interferon-gamma-secreting T cells specific for peptides derived from ESAT-6 and a second RD1 gene product, CFP10, were enumerated in 100 prospectively recruited healthy adults in Bombay (Mumbai), India. Eighty percent responded to >/=1 antigen, and many donors had high frequencies of T cells that were specific for certain immunodominant peptides. In contrast, of 40 mostly BCG-vaccinated, United Kingdom-resident healthy adults, none responded to either antigen. This study suggests an 80% prevalence of latent M. tuberculosis infection in urban India.